Comprehensive analysis reveals the underlying mechanism of arbuscular mycorrhizal fungi in kenaf cadmium stress alleviation. (February 2023) - Pan, Jiao; Cao, Shan; Xu, Guofeng; Rehman, Muzammal; Li, Xin; Luo, Dengjie; Wang, Caijin; Fang, Wangqiang; Xiao, Huiping; Liao, Changjun; Chen, Peng
Abstract: Soil Cadmium (Cd) contamination has become a severe environmental problem around the world. Kenaf has great potential for utilization and phytoremediation of soil contaminated with heavy metal. Arbuscular mycorrhizal fungi (AMF) can help plants alleviate Cd stress, but the underlying mechanism remains completely unknown. In this study, kenaf was inoculated or not inoculated with AMF at cadmium concentrations of 10 mg kg −1 and 50 mg kg −1 from the seedling stage to the vigorous growth stage. The results showed that AMF symbionts improved nutrient transport efficiency and significantly improved plant growth. Additionally, AMF colonization increased cell wall polysaccharide content which help to bind Cd in the cell wall and reduced the transport of Cd to aboveground plant tissues. The increase in soil pH (6.9), total balcomycin and easily extractable balcomycin content facilitated the chelation of metal by mycorrhizal fungi and reduced the biological effectiveness of Cd. Furthermore, AMF upregulated the expression levels of key kenaf genes, such as Hc.GH3.1, Hc.AKR, and Hc.PHR1, which plays an important role in enhancing kenaf Cd tolerance. Our findings systematically revealed the mechanisms by which AMF responds to Cd stress in kenaf, inoculation of AMF with kenaf could be used to enhance the removal of Cd from soil pollution in mining areas by phytoremediation. Graphical abstract: Image 1 Highlights: AMF can alleviate kenaf Cd stress by reducing oxidant damage, improving photosynthetic capacity, and nutrient uptake. AMF increase the polysaccharide content of cell wall to fix Cd in the roots and inhibit Cd transport to above ground plant parts. AMF enhance balcomycin content in soil which facilitates chelation and reduces the biological effectiveness of Cd. The up-regulation of the expression of genes, such as Hc.GH3.1, Hc.ARK, and Hc.PHR1, contribute to the kenaf Cd tolerance.